Impact of Grid-Scale Solar Photovoltaic Integration on Power System Performance - Sunday Ugwuanyi, Nnaemeka; Ugwuoke, Nestor Chima; Obi, Patrick Ifeanyi (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
The impact of SPV integration on grid performance is a topic of ongoing debate, with conflicting reports on its effects. This study employs modal analysis, Newton-Raphson power flow, and time-domain simulations to assess the effects of SPV integration on voltage profiles, active power loss, and system stability in the IEEE 4-machine and Nigerian 50-bus power systems. The findings reveal that SPV integration impacts power systems differently, emphasizing the need for a comprehensive approach that considers voltage stability, power losses, and stability constraints. While SPV integration can improve voltage levels and reduce power losses, it may also compromise transient stability, highlighting the importance of careful planning and grid reinforcement. For the IEEE 4-machine system, SPV integration is feasible up to 25% based on power loss, but transient stability constraints limit it to 0%. For the Nigerian grid, optimal SPV integration is achieved at 10% based on power loss and voltage profile, while transient stability constraints limit integration to 5%. This study underscores the necessity of a multi-metric approach to defining SPV penetration limits, considering the trade-offs between voltage performance, power loss, and system stability.